2006
DOI: 10.1111/j.1439-0450.2006.00906.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Antibodies to Pestiviruses in Goats in Austria

Abstract: Serological investigations were carried out to determine the prevalence of pestiviral infections in goats in Austria, and to investigate the possible relations to herd management practices. The prevalence of antibodies to pestiviruses was investigated in 549 goats in 80 flocks from four regions of Austria. The examination for antibodies was performed using an indirect enzyme-linked immunosorbent assay detecting antibodies to the border disease virus (BDV) and bovine viral diarrhoea virus (BVDV). The observed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 13 publications
2
24
0
2
Order By: Relevance
“…Herd seroprevalences are highly variable. In Austria, the average flock prevalence was reported to be 31.3% [24] but may be as high as 83% [27]. In several studies, the seroprevalence in goats was found to be significantly higher in herds that had contact to cattle [22,24,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herd seroprevalences are highly variable. In Austria, the average flock prevalence was reported to be 31.3% [24] but may be as high as 83% [27]. In several studies, the seroprevalence in goats was found to be significantly higher in herds that had contact to cattle [22,24,27].…”
Section: Introductionmentioning
confidence: 99%
“…In Austria, the average flock prevalence was reported to be 31.3% [24] but may be as high as 83% [27]. In several studies, the seroprevalence in goats was found to be significantly higher in herds that had contact to cattle [22,24,27]. Interestingly, compared to sheep where BDV antibodies are most prevalent, pestivirus antibodies in goats are more often not clearly specifiable or are rather directed against BVDV [25,27].…”
Section: Introductionmentioning
confidence: 99%
“…4,18 Goats have been reported to be infected with BVDV by natural transmission. 7,14,15,27 Seropositivity among goat populations varies around the world: 1.8% 7 to 16% in North America (1982)(1983) 15 ; 31.4% in Africa (1998) 27 ; and 11.5% in Europe, 2006.…”
mentioning
confidence: 99%
“…Em seis propriedades positivas houve apenas um animal soropositivo, e apenas um rebanho apresentou três animais soropositivos entre oito testados, com títulos de 40, 80 e 160 (dados não apresentados), o que sugere a infecção prévia destes animais por um pestivírus e possivelmente de animais com infecção aguda. Levando-se em consideração que nessa propriedade há criação consorciada de caprinos e bovinos, a transmissão pode ter ocorrido entre as espécies (LOKEN, 1995;KRAMETTER-FROETSCHER et al, 2010), e acredita-se que provavelmente os bovinos estejam atuando como fontes de infecção.…”
Section: Resultsunclassified
“…Em caprinos, a ocorrência de casos clínicos da infecção por Pestivirus é baixa, no entanto, a doença pode apresentar-se de forma branda a severa (KRAMETTER-FROETSCHER et al, 2006). Por outro lado, a ocorrência de animais PI garante a persistência do vírus nos rebanhos.…”
Section: Introductionunclassified